Environmental Determinants Of Soil-Transmitted Helminth Infections In Palembang Schoolchildren: A Spatial Analysis - Thia Prameswarie; Tarishah Jannah F; Ahmad Ghiffari; Putri Erlyn; Nurul Qamariah (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2026)
Soil-transmitted helminth (STH) infection remains a public health concern in tropical urban settings. Understanding its spatial distribution and relationship with environmental determinants is important for targeted control. This cross-sectional spatial study included 294 primary school children (grades III and IV) from 18 districts of Palembang, Indonesia. Schools and participants were selected using two-stage cluster sampling. Stool specimens were examined using the direct smear method with eosin staining. District-level population density, latrine coverage, and piped water access were obtained from official statistics. Spatial autocorrelation was assessed using Global Moran's I, Local Indicators of Spatial Association (LISA), and bivariate LISA. The overall STH prevalence was 16.7% (49/294 children). Most districts had low prevalence (<20%), while Ilir Barat Dua (41.2%), Ilir Barat Satu (35.3%), and Kertapati (29.4%) showed moderate prevalence (20-50%). Global Moran's I indicated significant positive spatial autocorrelation for latrine coverage (I = 0.190; p = 0.043), but not for population density (I = -0.135; p = 0.078) or piped water access (I = -0.049; p = 0.449). LISA mapping identified localized clusters of higher STH prevalence in areas with inadequate latrine coverage. STH endemicity in Palembang is low to moderate, but localized clusters remain. Sanitation, particularly latrine availability, was the main environmental factor associated with spatial clustering, whereas population density and piped water access showed no significant spatial association. Targeted sanitation improvement, hygiene education, and spatially guided surveillance are recommended.